Circular polarization in a non-magnetic resonant tunneling device - dos Santos, Lara F; Gobato, Yara Galvão; Teodoro, Márcio D; Lopez-Richard, Victor; Marques, Gilmar E; Brasil, Maria JSP; Orlita, Milan; Kunc, Jan; Maude, Duncan K; Henini, Mohamed; Airey, Robert J (Nanoscale research letters, 2011)
We have investigated the polarization-resolved photoluminescence (PL) in an asymmetric n -type GaAs/AlAs/GaAlAs resonant tunneling diode under magnetic field parallel to the tunnel current. The quantum well (QW) PL presents strong circular polarization (values up to -70% at 19 T). The optical emission from GaAs contact layers shows evidence of highly spin-polarized two-dimensional electron and hole gases which affects the spin polarization of carriers in the QW. However, the circular polarization degree in the QW also depends on various other parameters, including the g -factors of the different layers, the density of carriers along the structure, and the Zeeman and Rashba effects.